2009
DOI: 10.1590/s0102-09352009000400007
|View full text |Cite
|
Sign up to set email alerts
|

Fisioterapia após substituição artroscópica do ligamento cruzado cranial em cães: I - avaliação clínica, radiográfica e ultrassonográfica

Abstract: RESUMOForam avaliadas a aplicabilidade da cirurgia artroscópica na substituição do ligamento cruzado cranial (LCC) e o efeito da fisioterapia pós-operatória, por meio de exames clínicos, radiográficos e ultrassonográficos, em 16 cães sem raça definida, machos, com pesos entre 19,2 e 26,3kg, submetidos à ruptura experimental do LCC e subsequente substituição deste ligamento pelo enxerto autógeno da fascia lata. Os animais foram distribuídos em dois grupos de oito cada: no grupo I os cães foram submetidos ao pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
8
0
4
Order By: Relevance
“…Baraúna Júnior et al (2007), in an experiment on CCL stabilization in dogs using extracapsular femorofabelotibial interconnection technique, completed immediate postoperative cryotherapy for 48h and PJM for 4 weeks and observed functional improvement in the dogs after 180 days. On the other hand, Muzzi et al (2009) observed gradual improvement in the degree of lameness after only 30 days in an intracapsular technique study substituting CCL for autogenous fascia lata graft in dogs associated with a physical therapy program.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Baraúna Júnior et al (2007), in an experiment on CCL stabilization in dogs using extracapsular femorofabelotibial interconnection technique, completed immediate postoperative cryotherapy for 48h and PJM for 4 weeks and observed functional improvement in the dogs after 180 days. On the other hand, Muzzi et al (2009) observed gradual improvement in the degree of lameness after only 30 days in an intracapsular technique study substituting CCL for autogenous fascia lata graft in dogs associated with a physical therapy program.…”
Section: Resultsmentioning
confidence: 93%
“…All X-rays were digitized and evaluated by two examiners (1 and 2) in a blind study. The evaluations consisted of defining the X-ray image according to the classification of Muzzi et al (2009) as follows: 1 for femorotibiopatelar joint without alteration, 2 for discrete joint effusion alterations, discrete periarticular osteophyte formation at the patellar extremities, and caudal surface of the tibial condyles, 3 for moderate alterations, moderate joint effusion alterations, moderate periarticular ostephytes in the trochlear ridges of the femur, fabelo, fibula head, medial surfaces and/or lateral femoral condyles and 4 for accented alterations with formation of intra-joint ostephytes (the joint surface of the tibial plateau and intercondylar notch) and subchondral bone sclerosis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations